C.S. Lewis then and now - Kort, Wesley A. (New York : Oxford University Press, 2001)
Clive Staples Lewis (1898-1963) was a distinguished scholar of medieval and Renaissance literature, who taught at both Oxford University and Cambridge University. After his conversion to Christianity, Lewis began writing Christian apologetic works aimed at a popular audience. It is for these works that Lewis is now best remembered; especially in the US, where his books have sold in millions and continue to be popular. Perhaps because of this popularity, however, Lewis's Christian writings are generally dismissed by theologians as oversimplified and conceptually flawed. With this book, Wesley A. Kort hopes to rehabilitate Lewis and to demonstrate the value and continuing relevance of his work. Kort not only retrieves Lewis from the now-dated context of his writings, but also wrests him from the hands of evangelicals who have turned his word into gospel and mistaken his attacks on modernity for a retreat from the world.
Introduction -- Retrieval -- Reenchantment -- Houses -- Culture -- Character -- Pleasure -- Celebration -- Conclusion.
Includes bibliographical references (p. 173-189) and index.
Description based on print version record.
Keywords: Lewis, C. S. -- 1898-1963.; Lewis, C. S. -- 1898-1963 -- Contributions in theology; Lewis, C. S. -- 1898-1963 -- Public opinion; Electronic books